Polycystic hydatid disease in Brazil: report of five new human cases and a short review of other published observations - D'Alessandro,A. (1996)
This paper describes five additional Brazilian human cases of polycystic hydatid disease due to Echinococcus vogeli, reviews the previous cases reported in Brazil, including one report of E. oligarthus (20 in total), and some epidemiological aspects of this disease which is no longer a curiosity but rather a problem that is not medically easy to handle. Its presence should be expected in any rural area of the New World where humans have not eliminated wild felids/canids, bush dogs, pacas, agoutis and other wild rodents.